Russian Detective Studies in the First Half of the 20th Century - Petr A. Moiseev (Studia Litterarum, 2022)
The article examines the works of Russian literary critics of the first half of the 20th century, such as K. Chukovsky, V. Bryusov, V. Shklovsky, E. Lann, N. Berkovsky, E. Vinaver, S. Eisenstein. The author considers Shklovsky’s article “The Novella of Mysteries,” notes its advantages and disadvantages (in particular, indicates the absence of definition of mystery, which is the central concept in the article, as well as Shklovsky’s mixing of the genres of detective story, Gothic novel, sensational novel, etc.). The author indicates advantages of Berkovsky’s note “About the Soviet detective fiction,” in which the example of the novel by A. Tolstoy “Hyperboloid of the engineer Garin” indicates what what is not typical for detective story. The author demonstrates how Eisenstein created a comprehensive and elaborate theory of the detective genre; in particular the understanding of the famous director of the genre specifics (almost complete impossibility of connection between detective genre and “serious” content) and his reference to the detective story as an example of the need for the artist to “always know the station to which you hold the way.” The article is the first detailed analysis of the works of Russian researchers of detective fiction.